2018
DOI: 10.30827/digibug.54304
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Questioning: Exploring Student Interaction and Cognitive Engagement in Spanish and EMI University Lectures

Abstract: This paper reports on the findings of a contrastive study exploring the use of teacher questions to gauge their cognitive demand and potential for triggering interaction between classroom participants. The data consists of a corpus of 16 lectures given in Spanish and English (eight of each) from two subjects in a Business Administration degree. Results show similarities and differences in the use of teacher questions in Spanish and EMI contexts, and highlight the importance of language awareness to help lectur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
2
1
Order By: Relevance
“…These results differ from the ones obtained by Sánchez‐García (2018) who carried out a contrastive study analyzing the use of Spanish lecturers' questions in EMI and SMI in the Business Administration degree. The author concluded that there was no direct correlation between teacher questioning and interaction because several times these went unanswered.…”
Section: Introductioncontrasting
confidence: 99%
“…These results differ from the ones obtained by Sánchez‐García (2018) who carried out a contrastive study analyzing the use of Spanish lecturers' questions in EMI and SMI in the Business Administration degree. The author concluded that there was no direct correlation between teacher questioning and interaction because several times these went unanswered.…”
Section: Introductioncontrasting
confidence: 99%
“…In a study also based on naturally occurring data, Dafouz Milne and Núñez Perucha (2010) reported contrasting findings, identifying more explicitness in transition signaling in the Spanish-medium lectures, as well as more metadiscursive variety and specificity. Similarly, contrastive research on question use seems to suggest that the language switch affects the use of questions: frequency, type and purpose of questions all varied in various constellations in the shift between EMI and L1 classes (Arévalo, 2017;Sánchez-García, 2018, pointing at a significant role played by the context. Certainly, another potential influencing factor behind certain discursive choices could lie in the nature of the content; however, this aspect has received only modest attention in the literature.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Lasagabaster, 2022; Ibrahim & Ahmad, 2020;Molino, 2018) and questions (e.g., Chang, 2012;Milne and García, 2019;Genc & Yuksel, 2021;Hu & Li, 2017;Johnson & Picciuolo, 2020). However, contrastive studies comparing L1 and EMI lectures are still extremely scarce (Arévalo, 2017;Arkin & Osam, 2015;Costa & Mariotti, 2017;Dafouz Milne & Núñez Perucha, 2010;Sánchez-García, 2018Thøgersen and Airey, 2011; see also the seminal works of Crawford Camiciottoli, 2005;Vinke, 1995) and can vary in terms of analytical angle and criteria for data selection. Furthermore, the predominant focus on communicative practices has resulted in the role played by content being somewhat overlooked.…”
Section: Introductionmentioning
confidence: 99%